The Influence of LMX and EVB on Employee Performance with Job Satisfaction as a Mediator at PLN IP Suralaya - S Lubis, Irwan Edi; Damarwulan, Liza Mumtazah (Advances In Social Humanities Research, 2025)
The purpose of this research is to examine the influence of Leader Member Exchange (LMX) and Employee Voice Behavior (EVB) on Employee Performance with Job Satisfaction as an intervening variable at PT PLN Indonesia Power Business Unit Pembangkitan Suralaya. The population in this study were all employees of the goods and services procurement section of PT PLN Indonesia Power, Suralaya Generation Business Unit. Purposive sampling is used as a sampling method, which means that the sampling technique uses certain criteria. In this study, 30 people were taken as samples with the criteria being permanent employees at PT PLN Indonesia Power Suralaya Generation Business Unit who served in the Goods and Services Procurement section. The research method uses a quantitative method using SmartPLS 4. The research results show that Leader Member Exchange (LMX) has a negative effect on employee performance and also has a positive and significant effect on job satisfaction. Employee Voice Behavior (EVB) has a positive and significant effect on Job Satisfaction and also has a positive but not significant effect on Employee Performance, and Job Satisfaction has a positive and significant effect on Employee Performance.